AN ANALYSIS OF 2004 TURKISH SOCIAL STUDIES CURRICULUM IN THE LIGHT OF NEW MILLENIUM TRENDS - AKINOĞLU, ORHAN (SOC PERSONALITY RES INC, 2008)
The aim in this study was to determine and assess the learning areas, skills and values underlined in the 2004 social studies curriculum reform for primary education in Turkey. The study was undertaken in a qualitative manner based on analyses of the 2004 social studies teaching curriculum for 4th-7th grades. Data were collected through document analyses of the 2004 social studies curriculum. Findings indicated that the learning areas, skills and values underlined in the curriculum for primary education reflect mainly global connections, multidimensional thinking, active learning, social rationalization, business mentality, creativity, individualism and democratic consciousness.
Keywords: socialization; educational policy; primary curriculum; skills; values; social studies